Multilevel resistive switching in Ti/CuxO/Pt memory devices - Wang, Sheng-Yu; Huang, Chin-Wen; Lee, Dai-Ying; Tseng, Tseung-Yuen; Chang, Ting-Chang (My University, 2010)
The multilevel resistive switching (RS) behaviors of the Ti/CuxO/Pt device were investigated by controlling the operated parameters of current and voltage bias in this study. We demonstrated that at least five-level memory states for data storage could be determined by controlling the current compliance, the span of voltage sweeping, and the amplitude of voltage pulse imposed on the memory device. During the dc voltage sweeping mode, not only the multilevel ON-states but also the multilevel OFF-states were achieved for the multilevel storage. The RS mechanism of the Ti/CuxO/Pt device is proposed to be related to the formation/rupture of the conducting filaments, arising from the interfacial oxygen ion migration between the Ti top electrode and CuxO films. Moreover, a possible conduction scenario for the multilevel RS behaviors is also suggested. Owing to all the multilevel memory states are distinguishable and possess the nondestructive readout property, it implies that the Ti/CuxO/Pt device has the promising potential for the future multilevel-capability memory cell application. (c) 2010 American Institute of Physics. [doi:10.1063/1.3518514]